2016
DOI: 10.14202/vetworld.2016.1375-1380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aegle marmelos and Murraya koenigii in treatment of delayed pubertal buffaloes heifers

Abstract: Aim:This study aims to study the estrus induction, ovulation, and conception rate of delayed puberty in buffaloes heifers by feeding a herbal plants Aegle marmelos (bael/bili/bhel leaf) and Murraya koenigii (Curry leaf).Materials and Methods:Totally, 24 buffalo heifers with delayed puberty were selected for the present study and divided randomly in four equal groups (n=6). Before experiment, all animals were dewormed with albendazole at 10 mg/kg body weight to prevent them from the stress of parasitism. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Later in 2016, [26] obtained 51.51% of pregnant ewes following a treatment based on extracts of Aegle marmelos and Murraya koenigii against 16.7% of pregnant females that had not been treated. In buffalo, extracts of Aegle marmelos and Murraya koenigii have also been shown to be very effective not only for heat induction but also for the improvement of fertility with 75% and 33.33% of induced heat and 75% and 50% of pregnant females, respectively for the treatment and control batches [18]. With regard to the goat species, the work carried out by [15] showed that the combination of plant extracts from Murraya koenigii and Aegle marmelos improves the fertility of goats in anoestrus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later in 2016, [26] obtained 51.51% of pregnant ewes following a treatment based on extracts of Aegle marmelos and Murraya koenigii against 16.7% of pregnant females that had not been treated. In buffalo, extracts of Aegle marmelos and Murraya koenigii have also been shown to be very effective not only for heat induction but also for the improvement of fertility with 75% and 33.33% of induced heat and 75% and 50% of pregnant females, respectively for the treatment and control batches [18]. With regard to the goat species, the work carried out by [15] showed that the combination of plant extracts from Murraya koenigii and Aegle marmelos improves the fertility of goats in anoestrus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if it would be necessary to facilitate the introduction of artificial insemination in sheep and goats in Niger, it would be interesting, among other things, to seek a technique which induces heat in these females at a lower cost and which can also preserve the environment more through, for example, the use of extracts of natural plants. Already, tests carried out on the basis of several plant organs by many teams of researchers around the world have made it possible to obtain very encouraging results on the induction of heat both in laboratory animals and also in domestic animals [13,14,15,16,17,18,19]. It is in this order of idea that the present study is done specially to set up a heat induction system in goats from plants harvested in Niger.…”
Section: Introductionmentioning
confidence: 91%
“…Delayed attainment of puberty is one of the major reproductive problems in buffaloes. The incidence of delayed puberty in buffalo was reported as 33% in the farms maintained by marginal and sub marginal farmers (Honparkhe et al, 2019) which is significantly lower than the incidence reported in pubertal anestrus buffaloes (56%) (Baitule et al, 2016). Earlier it was observed that delayed pubertal animal show certain variation in plasma biochemical profile which may be attributed to the delay in puberty (Pothireddy et al, 2020;Ahuja and Parmar, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Different hormonal and non-hormonal methods have been tried to augment fertility in delayed pubertal buffalo heifers but with variable success rates (Naidu et al, 2009;Baitule et al, 2016). Estradoublesynch (Mirmahmoudi et al, 2014a) and progesterone based ovsynch protocols (Ghuman et al, 2015) have been used in post-partum anestrus and subestrous buffaloes; but the similar stud-ies using these hormonal protocols are lacking in delayed pubertal buffalo heifers.…”
Section: Introductionmentioning
confidence: 99%
“…Aegle marmelos (bel) and Murraya koenigii (curry), medicinal plants have currently drawnmany research attention for various reproductive ailments in farm animals (Mehrotra, 2002;Jondhale, 2007;Kumar, 2008, Dutt et al, 2010Kumar et al, 2016;Kumawat et al, 2016;Rautela et al, 2017Rautela et al, , 2018. Individually the medicinal plants M. koenigii (Mehrotra, 2002) and A. marmelos (Jondhale, 2007 andKumar, 2008) and in combination (Dutt et al, 2010;Kumar et al, 2016;Baitule et al, 2016) have been used to augment the reproductive function in laboratory rats and anestrus goats, cattle/buffalo.…”
Section: Introductionmentioning
confidence: 99%